Endothelial cell tetrahydrobiopterin deficiency attenuates LPS-induced vascular dysfunction and hypotension - Chuaiphichai, S; Starr, A; Nandi, M; Channon, K; McNeill, E (Elsevier, 2015)
Overproduction of nitric oxide (NO) is thought to be a key mediator of the vascular dysfunction and severe hypotension in patients with endotoxaemia and septic shock. The contribution of NO produced directly in the vasculature by endothelial cells to the hypotension seen in these conditions, vs. the broader systemic increase in NO, is unclear. To determine the specific role of endothelium derived NO in lipopolysaccharide (LPS)-induced vascular dysfunction we administered LPS to mice deficient in endothelial cell tetrahydrobiopterin (BH4), the essential co-factor for NO production by NOS enzymes. Mice deficient in endothelial BH4 production, through loss of the essential biosynthesis enzyme Gch1 (Gch1fl/flTie2cre mice) received a 24 hour challenge with LPS or saline control. In vivo LPS treatment increased vascular GTP cyclohydrolase and BH4 levels in aortas, lungs and hearts, but this increase was significantly attenuated in Gch1fl/flTie2cre mice, which were also partially protected from the LPS-induced hypotension. In isometric tension studies, in vivo LPS treatment reduced the vasoconstriction response and impaired endothelium-dependent and independent vasodilatations in mesenteric arteries from wild-type mice, but not in Gch1fl/flTie2cre mesenteric arteries. Ex vivo LPS treatment decreased vasoconstriction response to phenylephrine in aortic rings from wild-type and not in Gch1fl/flTie2cre mice, even in the context of significant eNOS and iNOS upregulation. These data provide direct evidence that endothelial cell NO has a significant contribution to LPS-induced vascular dysfunction and hypotension and may provide a novel therapeutic target for the treatment of systemic inflammation and patients with septic shock.